URGENSI PEMBENTUKAN UNDANG-UNDANG PROFESI KONSULTAN PAJAK DALAM MEWUJUDKAN PROFESIONALISME DAN KEPASTIAN HUKUM PERPAJAKAN DI INDONESIA - Daniel Lehman; Sudarto (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2025)
Tax consultants lack a comprehensive legal basis at the level of legislation. Current regulations remain at the Minister of Finance Regulation (PMK) level and inadequate general recognition in the Financial Sector Development and Strengthening Law (PPSK Law), raising issues of legal vulnerability and weak professional standards. This study aims to analyze the urgency of establishing a Tax Consultant Profession Law and identify compelling reasons behind the need for a specific law for tax consultants to achieve professionalism and legal certainty in taxation in Indonesia. This study employed normative legal methods with both statutory and conceptual approaches, and qualitative data analysis was conducted. The results indicate that the current regulation of tax consultants remains administrative in nature and does not provide legal protection. Tax consultants lack independent law enforcement status, legal immunity, or self-regulatory oversight mechanisms. As a result, they are vulnerable to criminalization, and oversight of the profession remains under the control of the government (the Ministry of Finance). The urgency of establishing a Tax Consultant Profession Law is high to enhance professionalism, provide clear legal protection for consultants and taxpayers, and create greater legal certainty in the tax system.